2009
DOI: 10.1017/s0142716408090073
|View full text |Cite
|
Sign up to set email alerts
|

The development of vocabulary in English as a second language children and its role in predicting word recognition ability

Abstract: Do older English as a second language (ESL) children have the same knowledge of word meanings as English as a first language (EL1) children? How important is vocabulary's role in predicting word recognition in these groups? This study sought to answer these questions by examining the profiles of ESL and EL1 upper elementary aged children, for a 2-year period starting in Grade 5. Multivariate analyses revealed that (a) EL1 and ESL groups did not differ on underlying processing components (e.g., phonological awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 98 publications
8
60
1
Order By: Relevance
“…Previous investigations of specific comprehension difficulties among monolingual students in late elementary school suggested that only a small percentage of students show specific comprehension deficits (Catts et al, 2005). However, the prevalence of specific comprehension deficits may be more common among English language learners (ELLs) because of relative skill deficits in vocabulary and listening comprehension (Jean & Geva, 2009; Mancilla-Martinez & Lesaux, 2010). Similar to monolingual students, these deficits in oral language skill may manifest in late emerging, specific comprehension difficulties (Nakamoto, Lindsey, & Manis, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of specific comprehension difficulties among monolingual students in late elementary school suggested that only a small percentage of students show specific comprehension deficits (Catts et al, 2005). However, the prevalence of specific comprehension deficits may be more common among English language learners (ELLs) because of relative skill deficits in vocabulary and listening comprehension (Jean & Geva, 2009; Mancilla-Martinez & Lesaux, 2010). Similar to monolingual students, these deficits in oral language skill may manifest in late emerging, specific comprehension difficulties (Nakamoto, Lindsey, & Manis, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In many Hong Kong preschool classrooms, the teaching of English emphasizes writing exercises and children in general have little exposure to oral language (limited to 40–60 min per week provided by NET in the English lesson times). ESL children have been reported to be lagging behind their L1 counterparts in vocabulary development (Jean & Geva, 2009). They are also less likely to learn vocabulary via incidental learning or text reading (Proctor, Carlo, August, & Snow, 2005), with explicit instruction needed (August, Carlo, Dressler, & Snow, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for analyzing four separate criterion measures was that the phonological loop has been related to early reading and language acquisition (word identification and word knowledge; e.g., Farnia & Geva, 2011;Jean & Geva, 2009;Kieffer & Lesaux, 2012), whereas the executive component of WM has been related to higher level processing such as reading comprehension and language production (e.g., Lesaux, Lipka, & Siegel, 2006;Swanson et al, 2011). The mixed regression analyses included computing a baseline model (unconditional means model) and three conditional models.…”
Section: Approach To Analysesmentioning
confidence: 99%